Power Control Techniques for Interference Management—A Systematic Review - Nthambeleni Reginald Netshikweta; Mbuyu Sumbwanyambe (Telecom)
Applying optimal power control techniques in wireless networks is invaluable to mitigating interference among mobile devices. This review seeks to evaluate the depth and extent of the application of power control in 5G wireless networks through a systematic literature review. This review includes journal articles from 2018 to 2023 indexed in the Scopus, Web of Science (WoS), and IEEE Xplore databases. We used the following search string to search articles from each database: (*power control” AND “resource management” OR interference management AND 5G mobile communication). We obtained 3561 articles from the Scopus, WoS, and IEE Xplore databases with respective counts of 254, 728, and 2579. We paid attention to journal articles to ensure the quality of the review. After carefully assessing each record, we selected 770 journal articles using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Using R package software, we performed analyses based on the number of citations, keyword co-occurrence, and trending topics. This review reveals that various power control taxonomies address interference in 5G wireless networks. The results confirm continuous growth in the study, signifying the need for further exploration.